How much Indonesian science and biology teachers in different educational levels should mastering the genetics? - Susanti Wulandari; Ari Widodo; Nuryani Yogipratana Rustaman; Kalsom Binti Badrus (Universitas Muhammadiyah Malang, 2025)
Teachers are professional educators who must meet academic qualifications, competencies, and educator certificates. The phenomenon in the field, non-science teachers who teach science subjects still found and it was affect the learning process. Genetics is one of the contents in biology which familiar as a difficult content by students. This is due to the weak mastery of the depth and breadth of material content at every level of education. This study examines the depth and breadth of mastery of the genetics content required for teachers at various levels of education. This study uses a qualitative approach with the grounded theory method. The researcher collected data in stages, namely data collection from teachers and experts. The data collection process was carried out for 15 months and involving 15 participants form nine teachers and six biology experts. The data analysis process in grounded theory research goes through three stages, namely open coding, axial coding, and selective coding. Based on the findings of this study, the depth and breadth of genetics content that must be mastered by teachers at each level of education is different. A new theory has been successfully synthesized, namely that the higher the level of education, the higher the depth and breadth of content that must be mastered by a teacher. In this case, it means that the depth of content (vertical dimension) and breadth of content (horizontal dimension) are directly proportional to the level of education.